pT <=>\(\frac{x^4}{\left(x-2\right)^2}+\frac{x^2}{x-2}-2=0\)
đk: x khác 2
Đặt \(\frac{x^2}{x-2}=t\)
Ta có phương trình:
\(t^2+t-2=0\Leftrightarrow t^2+2t-t-2=0\Leftrightarrow t\left(t+2\right)-\left(t+2\right)=0\Leftrightarrow\left(t+2\right)\left(t-2\right)=0\)
<=> \(\orbr{\begin{cases}t=2\\t=-2\end{cases}}\)
Với t=2 ta có:
\(\frac{x^2}{x-2}=2\Leftrightarrow x^2=2x-4\Leftrightarrow x^2-2x+4=0\Leftrightarrow\left(x-1\right)^2+3=0\)vô lí
Với t=-2:
\(\frac{x^2}{x-2}=-2\Leftrightarrow x^2=-2x+4\Leftrightarrow x^2+2x=4\Leftrightarrow\left(x+1\right)^2=5\Leftrightarrow\orbr{\begin{cases}x+1=\sqrt{5}\\x+1=-\sqrt{5}\end{cases}}\)
<=> \(\orbr{\begin{cases}x=-1+\sqrt{5}\\x=-1-\sqrt{5}\end{cases}}\)(tm)
Vậy...